Obesity and Its Relation to Chronic Kidney Disease: A Population-Based, Cross-Sectional Study of a Thai Population - Bancha Satirapoj; Ouppatham Supasyndh; Amnart Chaiprasert; Prajej Ruangkanchanasetr; Naowanit Nata; Inseey Kanjanakul; Panbuppa Choovichian (The Korean Society of Nephrology, 2012)
Obesity represents a significant problem in patients with cardiovascular disease and chronic kidney disease (CKD). We investigated the association between body mass index (BMI) and CKD in Thai individuals. Participants underwent general health screening. Overweight, weight at risk, obese I and obese II were defined as having a BMI ≥23 kg/m2, 23-24.9 kg/m2, 25-29.9 kg/m2 and ≥30 kg/m2, respectively. CKD was defined as a glomerular filtration rate (GFR) <60 mL/min/1.73 m2. An estimate of the GFR was obtained by the four-variable Modification of Diet in Renal Disease (MDRD) equation. The study population had 12,348 males and 3,009 females. The survey population had a 14.5% prevalence of CKD. There was also a significant graded relationship between the degrees of overweight with the prevalence of CKD. Mean BMI were 25.06±3.29 kg/m2 for CKD subjects and 23.98±3.11 kg/m2 for non CKD subjects (P<0.001). Prevalence of overweight and abdominal obesity in the participants with CKD were found to be higher than in those without CKD (overweight, 74.6% vs. 61.3%, P<0.001; abdominal obesity, 28.3% vs. 25.7%, P=0.009). In a multivariate logistic regression analysis; weight at risk (adjusted odds ratio 1.19; 95% CI 1.04-1.37), obese I (adjusted odds ratio 1.44; 95% CI 1.26-1.64), and obese II (adjusted odds ratio 1.99; 95% CI 1.59-2.48) were associated with CKD. In conclusion, our data supported that overweight and obesity were associated with increased risk for CKD in Thai individuals undergoing a general health screening, independently of age, gender, blood pressure, serum lipid, uric acid, and glucose levels.